(3GdJbQjQGJs - (3GdcdHGSj GdfLaj, eMeO EHQGgje Hf MSjf GdcdHGSj GdfLaj, hdO SfI (B1322(3g`s ((3HNW GdeDdas)
(3ChdgG (B:s
(3ChdgG(B: (3bhdg aj GdaUd GdKGfj (B... (3gPG gh GdUMjM GdPj dG QjH ajg EP djS aj GdHjf LYd daX deYfi de jJHYg GdGSJYeGd djchf Pdc SHH aj chf GddaX MbjbIs
(3BNQgG (B:s
(3BNQgG(B: (3hgh Cfg HYO Cf aQVf YOe GdOYGA HjfgeG hLhOG Hd (B.. (3HjfgeG GjLGOG hgh GTcGd BNQ (B... (3hSjCJj GdcdGe Ydjg Ef TGA Gddgs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdPQjYI, L (B4: 268s
(3GdPQjYI, L (B4: 268s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
(3ehGUaGJ GdhYGA (B:s
Keywords: (3CUhd Gdabgs